The Struggle of Women for their Political and Social Rights in Britain in the Twentieth Century - Ahmid, Kellal, Nadjet Khaoula (جامعة الوادي University of Eloued, 2019)
This dissertation is a comprehensive study which explores the history of women in Britain during the twentieth century in which women had a long road of struggle for their political and social rights so that they could obtain equal rights-which were deprived of for many centuries and specifically during the reign of Queen Victoria- as men do. This study attempts to reveal the real suffering women had gone through to gain their freedom with all its aspects either politically such as the right to vote or socially such as the right of being regarded as individuals and not as servants. Thus, the research aims to highlight the radical changes that women brought to the British history as well as to their societies through adopting different strategies whether peacefully or aggressively. The methodology that has been adopted in this research is analytical description by which the researchers have provided a thorough description of women’s political and social strife and a qualitative analysis of short corpus composed of articles, letters and quotes related to certain eminent females who have made changes in the British history. The main conclusion drawn from this research is that women’s efforts were effective in many ways in which they have upgraded their position from hardship to prosperity.Their efforts were acquainted with endless sufferance which results in the removal of the majority, if not all, the stereotypical images in the society and in having mostly equal rights as men have. Further research is needed to identify other achievements and victories -females had reached- for the sake of reviving women’s legacy over the centuries. تتناول هذه الأطروحة دراسة شاملة حول تاريخ المرأة في بريطانيا خلال القرن العشرين, حيث خاضت النساء كفاحا طويلا طلبا لحقوقهن السياسية والاجتماعية, حتى تتمكن في نهاية المطاف من الحصول على حقوق-حرمت منها لعدة قرون وبالتحديد خلال حكم الملكة فيكتوريا- متساوية مع الرجل. فمن أهم المواضيع التي تم التطرق اليها في هذا البحث هي مسألة اظهار المعاناة الحقيقية التي مرت بها النساء من اجل نيل حرياتهن مثل الحق في التصويت و الحق في اعتبارهن فرداً ضمن المجتمع لا كالخدم. وبالتالي، يهدف هذا البحث إلى تسليط الضوء على التغييرات الجذرية التي أحدثتها النساء عبر التاريخ البريطاني وكذا على مجتمعاتهن من خلال تبني استراتيجيات مختلفة سلمية كانت أم عدوانية. ولقد اعتُمد في هذه الدراسة على منهجية ذات وصف تحليلي , حيث قدم الباحثون وصفًا دقيقًا للنزاع السياسي والاجتماعي الذي خاضته المرأة بالإضافة الى تحليل نوعي لمجموعة صغيرة مكونة من مقالات ورسائل و اقتباسات ذي صلة ببعض النسوة البارزات اللاتي أحدثن تغييرات عبر التاريخ البريطاني. وفي الاخير, تم التطرق الى عرض النتائج الرئيسية التي استخلصت من هذه الاطروحة والتي من اهمها أن جهود المرأة كانت فعالة في نواحي متعددة ؛ فعلى سبيل المثال أنها رفعت مكانتها من الخضوع إلى الاجلال حيث كانت جهودها مصحوبة بمعاناة لا نهاية لها والتي أدت إلى إزالة غالبية الصور النمطية في المجتمع –إن لم تكن كلها- كما أن تلك الجهود أثمرت في نيلها جُل الحقوق التي يتمتع بها الرجال. وتبقى الحاجة الى مزيد من الدراسات المتواصلة حول هذا الموضوع لتحديد الإنجازات والانتصارات الأخرى - التي حققتها الإناث - من أجل إحياء إرث المرأة على مر القرون.
Keywords: Britain, Political Rights, Social Rights, the Twentieth Century, and Women’s Struggle.; الحقوق الاجتماعية ، الحقوق السياسية ، القرن العشرون ، بريطانيا ، كفاح المرأة